Hospitalization and Mortality in Patients With Heart Failure Treated With Sacubitril/Valsartan vs. Enalapril: A Real-World, Population-Based Study - Pathadka, Swathi; Yan, Vincent K. C.; Li, Xue; Tse, Gary; Wan, Eric Y. F.; Lau, Hayden; Lau, Wallis C. Y.; Siu, David C. W.; Chan, Esther W.; Wong, Ian C. K. (Frontiers in Cardiovascular Medicine, 2021)
Background: The effect of sacubitril/valsartan on survival and hospitalisation risk in older patients with heart failure has not been explored. We aimed to investigate the risk of hospitalisation and mortality with the use of sacubitril/valsartan versus enalapril in patients with heart failure. Methods: This was a population-based cohort study using the Hong Kong-wide electronic healthcare database. Patients diagnosed with heart failure and newly prescribed sacubitril/valsartan or enalapril between July 2016 and June 2019 were included. The risk of primary composite outcome of cardiovascular mortality or heart failure-related hospitalisation, all-cause hospitalisation, heart failure-related hospitalisation, cardiovascular mortality and all-cause mortality were compared using Cox regression with inverse probability treatment weighting. Additional analysis was conducted by age stratification. Results: Of the 44,053 patients who received sacubitril/valsartan or enalapril, 3,287 new users (sacubitril/valsartan, n=1,056; enalapril, n=2,181) with a diagnosis of heart failure were identified. Compared with enalapril, sacubitril/valsartan users were associated with a lower risk of primary composite outcome (hazard ratio [HR] 0.58; 95% confidence interval [CI], 0.45-0.75), heart failure-related hospitalisation (HR 0.59; 95% CI, 0.45-0.77), all-cause mortality (HR 0.51; 95% CI, 0.36-0.74) and borderline non-significant reductions in all-cause hospitalisation (HR 0.85; 95% CI, 0.70-1.04) and cardiovascular mortality (HR 0.63; 95% CI, 0.39-1.02). The treatment effect of sacubitril/valsartan remains unaltered in the patient subgroup age ≥ 65 years (73%). Conclusions: In real-world settings, sacubitril/valsartan was associated with improved survival and reduced heart failure-related hospitalisation compared to enalapril in Asian patients with heart failure. The effectiveness remains consistent in the older population.